Genetic research and testing in sport and exercise science: A review of the issues - Wackerhage, H.; Miah, A.; Harris, R. C.; Montgomery, H. E.; Williams, A. G. (Journal of Sports Sciences, 2009)
This review is based on the BASES position stand on "Genetic Research and Testing in Sport and Exercise Science". Our aims are first to introduce the reader to research in sport and exercise genetics and then to highlight ethical problems arising from such research and its applications. Sport and exercise genetics research in the form of transgenic animal and human association studies has contributed significantly to our understanding of exercise physiology and there is potential for major new discoveries. Researchers starting out in this field will have to ensure an appropriate study design to avoid, for example, statistically underpowered studies. Ethical concerns arise more from the applications of genetic research than from the research itself, which is assessed by ethical committees. Possible applications of genetic research are genetic performance tests or genetic tests to screen, for example, for increased risk of sudden death during sport. The concerns are that genetic performance testing could be performed on embryos and could be used to select embryos for transplantation or abortion. Screening for risk of sudden death may reduce deaths during sporting events but those that receive a positive diagnosis may suffer severe psychological consequences. Equally, it will be almost impossible to keep a positive diagnosis confidential if the individual tested is an elite athlete.